2001
DOI: 10.1501/eczfak_0000000357
|View full text |Cite
|
Sign up to set email alerts
|

Akilci İlaç Kullanimi Üzeri̇nde Bi̇r Pi̇lot Çalişma : A Pilot Study on Rational Drug Use

Abstract: ÖZET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…AİKÖ'nün kullanıldığı bir çalışmada benzer sonuçlar elde edilmiş, araştırmaya katılanların %80'inin sadece hekimlerin ilaç önerisinde bulunacağı önermesine doğru cevap verdiği görülmüştür (10). Ankara'da hastane eczanesine başvuran hastalar ile yapılan çalışmada ise, %75,5 olarak saptanmıştır (11).…”
Section: Discussionunclassified
“…AİKÖ'nün kullanıldığı bir çalışmada benzer sonuçlar elde edilmiş, araştırmaya katılanların %80'inin sadece hekimlerin ilaç önerisinde bulunacağı önermesine doğru cevap verdiği görülmüştür (10). Ankara'da hastane eczanesine başvuran hastalar ile yapılan çalışmada ise, %75,5 olarak saptanmıştır (11).…”
Section: Discussionunclassified
“…17 It has been reported that 75.5% of outpatients in a hospital in Ankara used self-medication. 11 In studies conducted in Nigeria and India on patients who applied to the dentist, the rates of self-use of home remedies for dental problems were reported as 41.5% and 33.3%, respectively. 18,19 This rate was reported as 21.1% in patients who applied to a dentistry faculty in Türkiye.…”
Section: Discussionmentioning
confidence: 99%
“…The RDU process requires all health professionals (physicians, pharmacists, and other health personnel), society, the government and, the pharmaceutical industry to act rationally and contribute. 11 Although research on the determination of the problems related to RDU is frequently carried out today, the number of these studies is quite limited in dentistry. 12 In this study, it was aimed to determine the knowledge and attitudes of patients who applied to the oral and maxillofacial surgery clinic about RDU and to reveal whether the knowledge and attitudes about RDU differ according to demographic characteristics.…”
mentioning
confidence: 99%
“…Hastane eczanesine gelen hasta sayısının çok fazla olması ve bu nedenle eczacıya ulaşmanın çok güç olmasına bağlı olarak, eczacının yeterince danışmanlık yapamadığı gözlenmiştir. 23 Eczacıya danışmada kullanılan iletişim yöntemleri farklılıklar göstermektedir. 21 Hastaların ya-rısından fazlasının eczacısına danışmak için bir iletişim aracı kullandığı ve genç hastaların yaşlı hastalardan, eğitim düzeyi yüksek olan hastaların daha düşük olanlardan ve bekâr hastaların evli hastalardan daha fazla kullandığı gözlenmiştir.…”
Section: Veri̇ Anali̇zi̇unclassified